Epidemiological investigation and analysis of the genetic evolution of duck circovirus in China, 2022 - Peidong Li; Fuyou Zhang; Chunyang Bao; Hongmei Liu; Kai Yu; Hao Zhu; Xue Wang; Ke Shen; Tianyao Yang; Qingqing Song; Zhaoyang Li; Chunguo Liu (PLoS ONE, 2025)
Duck circovirus (DuCV) infection is an immunosuppressive disease that affects ducks and causes severe damage to their immune system. To elucidate the epidemiological characteristics of DuCV infection in China, a total of 2944 waterfowl samples were collected from 17 provinces from January to October 2022, and 612 DuCV-positive samples were identified. A descriptive statistical analysis was subsequently conducted. Furthermore, 51 near-full-length DuCV genome sequences were obtained, and molecular genetic evolution and recombinant analyses were performed. Geographically, Fujian Province had the highest rate of DuCV positivity (54.8%), followed by the Guangxi Zhuang Autonomous Region (30.4%). The rate of DuCV positivity was highest in samples from 21–40-day-old ducklings, accounting for 66.5% of the total positive samples. The most common pathogen involved in mixed infections with DuCV was parvovirus or Riemerella anatipestifer. Genetic and evolutionary analyses of the full genome sequences of 51 DuCV strains revealed that DuCV-1b and DuCV-2c were the most prevalent strains in China. Genetic recombination analysis suggested that the major parental sequences involved in the recombination of DuCV strains in ducks are present in Anhui, Sichuan, Shandong, and Guangxi. In addition, DuCV recombination events have occurred between strains with different genotypes or strains isolated from different countries. In summary, the DuCV epidemic in China is complex. There are two main co-circulating genotypes, those of the DuCV-1b and DuCV-2c strains, and coinfection of DuCV with other pathogens is a very common phenomenon in clinical practice. There is an urgent demand for vaccines against DuCV, and the protective efficacy of these vaccines against different DuCV genotypes needs to be carefully evaluated.